DESIGN FOR SIX SIGMA METHOD APPLICATION FOR CONCEPTUAL DESIGN OF MINING INFORMATION SYSTEM PT. KIDECO JAYA AGUNG - Parulian, Boy; Ginardi, R.V. Hari; Wijayaningtyas, Maranatha (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Nasional (ITN) Malang, 2024)
Although coal mining business provide a large economic contribution, coal mining operational can have negative impacts if that business don’t implement good mining practice. Therefore, companies need to optimize technology to minimize negative impacts and increase productivity. The problems that have occurred at PT. Kideco Jaya Agung is an information system that is currently implemented is not yet relevant according to the stakeholders expectation. Data error, bugs, and mistake found, so there will be potential for dualism point of view which can impact to fault in decision making. So strategic planning in information system is needed with the aim that the company designs a concept which is effective and has the best quality in accordance with stakeholder needs to support the company's business. The application of Design For Six Sigma (DFSS) is to analyze planning based on stakeholder needs, then the used tools is Software Quality Function Development (SQFD). SQFD tool quantifies user needs and then prioritizes the digitalization project portfolio by mapping all user needs involved in the business process. Design For Six Sigma analysis produces output analysis of stakeholder needs. Based on stakeholder needs, the business processes required to be digitized include Coordination Meetings, Data Analysis, Daily/Weekly/Monthly Reports, Contractor/Subcont Management, and Decision Making which then become a reference in designing data flow diagrams as conceptual design.